Thermal Analysis of Convective-Radiative Fin with Temperature-Dependent Thermal Conductivity Using Chebychev Spectral Collocation Method - George Oguntala; Raed Abd-Alhameed (Journal of Applied and Computational Mechanics, 2018)
In this paper, the Chebychev spectral collocation method is applied for the thermal analysis of convective-radiative straight fins with the temperature-dependent thermal conductivity. The developed heat transfer model was used to analyse the thermal performance, establish the optimum thermal design parameters, and also, investigate the effects of thermo-geometric parameters and thermal conductivity (nonlinear) parameters on the thermal performance of the fin. The results of this study reveal that the rate of heat transfer from the fin increases as convective, radioactive, and magnetic parameters increase. This study finds good agreements between the obtained results using the Chebychev spectral collocation method and the results obtained using the Runge-Kutta method along with shooting, homotopy perturbation, and Adomian decomposition methods.